Spatial transmission of resilience loss in deltaic dynamic systems - Yajun Wang; Jianliang Lin; Yu Yan; Zhenzhong Zeng; Xiaoye Liu; Shuxian Wang; Zhenyan She; Zeqin Huang; Pengnan Sun; Tongtiegang Zhao; Kairong Lin; Giovanni Coco; et al. (Communications Earth & Environment)
Abstract River and tidal dynamics regulate delta water levels, underpinning their ecological and socio-economic stability. Deltaic water level resilience, the capacity to recover from disturbances, is vital amid growing climate and human pressures, necessitating a robust method to quantify and monitor it. Here we define water level resilience as the rate of water level recovery post-hydrodynamic disturbances. We quantify resilience trends using autocorrelation and propose a high-dimensional resilience transmission method based on a vine Copula model to estimate the spatial propagation of resilience loss across subsystems. Applying this framework to the Pearl River Delta in China reveals spatial heterogeneity and inter-subsystem transmission of resilience loss driven by anthropogenic activities. Our approach can be extended to other major deltas, despite differing hydrodynamic and human impacts. The findings underscore the need for tailored management strategies addressing specific drivers and subsystem interactions, offering critical insights into the global delta preservation amid escalating environmental challenges.